Biochemical and hematological characterization of pirarucu (Arapaima gigas Schinz, 1822) juveniles fed with different nutritional feeding systems - Hashimoto, Alexandre Junior; Rocha, Ana Sabrina Coutinho Marques; Hurtado, Fernanda Bay; Viana, Geysa Almeida; Medeiros, Ivan Dias de; Porto, Marlos Oliveira; Dantas Filho, Jerônimo Vieira; Cavali, Jucilene (Acta Scientiarum. Animal Sciences, 2024)
The aimed of this study was to evaluate the influence of dietary protein levels on the biochemical and hematological parameters of pirarucu (Arapaima gigas). A total of 60 pirarucus specimens were used with an initial average weight of 499 ± 36 g and an initial average length of 40.30 ± 10.10 cm, stocked with densities of four pirarucus per fish tank network 48 m2 of water surface. Feed was provided three times a day (8 am, 1 and 6 pm), with five different levels of crude protein (CP) in diet: 34, 36; 38 and 40 and 45% CP. The fish were euthanized at 310 experimental days with an average of 8.0 ± 1.0 kg of body weight. Blood samples were collected by tail vessel venipuncture, divided into two aliquots 2 mL and used for determination of biochemical levels and blood count. The results were submitted to analysis of variance and regression for CP levels, with the results showed as averages followed by the standard deviation. Orthogonal contrasts were applied to verify linear and quadratic effects at 5% significance. It was observed that the parameters referring to the blood count, given by erythrocytes, hemoglobin, packed cell volume, MCV, HCM, CHCM, glucose and total proteins showed no differences between the different diets. The average values of total proteins were 3.80 ± 0.30 g L-1, glucose and triglycerides shown averages 43.45 ± 5.65 and 56.98 ± 5.80 mg dL-1, respectively. The maximum cholesterol level 120.00 ± 13.33 mg dL-1 was obtained at the 35.4% CP level in the growth phase. Protein levels in diet influenced the cholesterol levels in the pirarucu growth phase, however, they did not influence the other biochemical and hematological parameters.